Uji Aktivitas Antidiabetes Fraksi dari Ekstrak Etanol Daun Karamunting (Rhodomyrtus tomentosa (Ait.) Hassk.) Terhadap Mencit Diabetes - Novia Sinata (JURNAL FARMASI GALENIKA, 2016)
Diabetes mellitus is a disease characterized by blood sugar levels that exceed normal (hyperglycemia) as a result of the body is insulin deficiency relative or absolute. Karamunting (Rhodomyrtus tomentosa (Ait.) Hassk.) one of the plants that are traditionally used to treat diabetes mellitus. The antidiabetic activity of plant karamunting because this plant contains chemical compounds, one of which is flavonoid. The Antidiabetic research of fraction of the ethanol extract of the leaves Karamunting (Rhodomyrtus tomentosa (Ait.) Hassk ) has been done on white male mice induced diabetes by alloxan dose of 200 mg / kg body weight intraperitoneally. The fraction of the extract ethanol was given ethyl acetate fraction, fraction of n-hexane and the fraction of water with each dose of 25 mg/ kg body weight given orally once daily for seven days. Parameters measured were blood glucose levels in mice. The results showed that the fraction of water orally showed a decrease in blood glucose levels are higher than diabetic mice by fractions of ethyl acetate and n-hexane fraction orally. The percentage of blood glucose lowering effect of the water fraction of 58.87%, 52.09% fraction of ethyl acetate and hexane fraction 24.30%.